INOVASI DOMPET DARI KRESEK BEKAS UNTUK MENINGKATKAN DIMENSI KREATIF DAN GOTONG ROYONG SISWA SD - Fatma Nurmala, Asih; Insanul Qisti Bariyah; Sutrisna Wibawa (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research aims to determine the innovation of wallets made from used plastic bags to increase the creative dimension and mutual cooperation for elementary school students. The creative and mutual cooperation dimensions are dimensions of the Pancasila student profile in the independent curriculum currently being implemented. Utilizing used plastic bags into wallets also supports P5 activities in elementary schools. The method used is descriptive qualitative. Data collection techniques use observation, performance and documentation. This research produces innovative learning media that has sales value, namely wallets made from used plastic bags. The research subjects were sixth grade elementary school students who were in phase C. The research results showed that using used plastic bags into wallets could increase the creative dimension and mutual cooperation for elementary school students. The use of used plastic bags has a positive impact on elementary school students because it increases the creative dimension and mutual cooperation and produces items of selling value, namely wallets. Researchers recommend that this research can adopt similar activities for elementary school students. This activity is an activity that explores students' abilities in terms of creativity and mutual cooperation.